2020
DOI: 10.1101/2020.07.29.20164020
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Metformin Use Is Associated With Reduced Mortality in a Diverse Population With Covid-19 and Diabetes

Abstract: BACKGROUND: Coronavirus disease-2019 (COVID-19) is a growing pandemic with an increasing death toll that has been linked to various comorbidities as well as racial disparity. However, the specific characteristics of these at-risk populations are still not known and approaches to lower mortality are lacking. METHODS: We conducted a retrospective electronic health record data analysis of 25,326 subjects tested for COVID-19 between 2/25/20 and 6/22/20 at the University of Alabama at Birmingham Hospital, a tertia… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
104
1
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 72 publications
(115 citation statements)
references
References 28 publications
8
104
1
2
Order By: Relevance
“…Importantly, data on BMI were missing in more than 90% of the patients [30] . A large retrospective electronic health record data analysis in > 25,000 subjects tested for COVID-19 (n = 604 positive cases) found that metformin use was associated with reduced mortality in 239 subjects with diabetes and COVID-19 (OR: 0.38 [0.17−0.87]) [31] . Indeed, a large body of evidence suggests that obesity is associated with more severe clinical course of COVID-19 including higher mortality rate.…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, data on BMI were missing in more than 90% of the patients [30] . A large retrospective electronic health record data analysis in > 25,000 subjects tested for COVID-19 (n = 604 positive cases) found that metformin use was associated with reduced mortality in 239 subjects with diabetes and COVID-19 (OR: 0.38 [0.17−0.87]) [31] . Indeed, a large body of evidence suggests that obesity is associated with more severe clinical course of COVID-19 including higher mortality rate.…”
Section: Discussionmentioning
confidence: 99%
“…The available data from observational and retrospective studies showed controversial results regarding the association between metformin use and clinical adverse outcomes in patients with DM and COVID-19. Some studies showed no definite association between metformin use and clinical outcomes, including survival, and raised concerns about the possible risk of lactic acidosis in cases of multiple organ failure [ [13] , [14] , [15] ], while others reported that metformin use was associated with a higher risk of disease progression in patients with COVID-19 with DM during hospitalization [ 16 ]. However, five studies with a total of 6937 patients showed that metformin use was associated with reduction in mortality rate from COVID-19 infection [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…Crouse and colleagues retrospectively analyzed outcomes using electronic health records at the University of Alabama from February 25 to June 22, 2020, identifying 604 individuals with COVID-19 (40% with T2D). While prior use of insulin did not impact clinical outcomes, antecedent metformin use (n = 76) prior to the diagnosis of COVID-19 was associated with a 50% reduction in mortality, relative to non-metformin-treated subjects, findings not explained by between-group differences in %HbA1c or BMI ( Crouse et al., 2020 ). A putative benefit of antecedent metformin use in the US was also inferred from a retrospective analysis of health care claims data from January 1 to June 7, 2020, identifying 6,256 individuals hospitalized with COVID-19 (40.7% with T2D or obesity) in the United Health Group Clinical Discovery database ( Bramante et al., 2021 ).…”
Section: Glucose-lowering Therapies and Covid-19 Outcomesmentioning
confidence: 97%